Food trade in Bangladesh, India and Nepal - Ajmani, Manmeet Singh; Choudhary, Vishruta; Kishore, Avinash; Roy, Devesh (International Food Policy Research Institute, 2019)
Food and agricultural trade among different parts of the world can increase access to a wider variety and better quality of agricultural inputs and foods to farmers and consumers at lower prices and increase incomes of farmers and other participants in the value chain. This report* looks at the extent of food trade in Bangladesh, India and Nepal (BIN) among themselves and with the rest of the world using trade data from UN Comtrade (United Nations 2019) from 1996 to 2016. We also food trade in BIN with the neighbouring ASEAN countries who also have high dependence on agriculture. Food here includes a) cereals and vegetables, b) live animals and animal-based and c) processed foods. There is a lot of informal, undocumented trade across the 1751 km long open border between India and Nepal and the 4097 km porous Bangladesh-India border. However, our analysis covers only the formal trade because we do not have reliable estimates of the volume and the value of the informal food trade in the region. .